1934
DOI: 10.1017/s0016756800093146
|View full text |Cite
|
Sign up to set email alerts
|

On the Marine Gravels at March, Cambridgeshire

Abstract: Since the Fenland Research Committee was formed in 1932, several papers have appeared, under its auspices, describing recent research work in the Fen District. The present article is a contribution to the work of this Committee, but describes deposits which are earlier in date than those which have been dealt with so far. The marine gravels have long been known near the town of March in Cambridgeshire, and the object here is to collect what is known up to the present (1934) about this deposit and to discuss it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…To such a late, paradoxically cool transgression we might attribute such well known or much studied deposits as: -The March gravels (Baden-Powell 1934); with shells suggesting a sea level approximately 10 m above O.D. but temperatures a few "C lower than today's.…”
mentioning
confidence: 99%
“…To such a late, paradoxically cool transgression we might attribute such well known or much studied deposits as: -The March gravels (Baden-Powell 1934); with shells suggesting a sea level approximately 10 m above O.D. but temperatures a few "C lower than today's.…”
mentioning
confidence: 99%
“…), in the Mepal depression (to a height of −0.5 O.D.) and at March, the ‘type site’ of the March Gravels [ 113 ] (to a height of 5 m O.D.). There are Devensian solifluction sediments and Devensian late-glacial organic deposits in the Mepal depression which demonstrate a complex history of the former valley of the River Great Ouse, which resulted in the diversion of the river westwards of Chatteris in the later Devensian [ 83 ], as described above.…”
Section: Gravel Spreads In the Area Of The Tottenhill Glaciationmentioning
confidence: 99%
“…Baden-Powell (1934) was specifically interested in this question in his paper on the March gravels in Cambridgeshire. He noted that smaller specimens of Corbicula from fluvial sediments near Cambridge, such as those from Barnwell, had a smaller height in proportion to their length than the smaller specimens from the 'marine bed at Manea ' (p. 207).…”
Section: Ecological and Palaeoclimatic Significancementioning
confidence: 99%
“…Gardner observed that English Pleistocene Corbicula specimens are comparable to C. consobrina, rather than to C. artini, but she was apparently familiar only with shells from the Cambridge area. Baden-Powell (1934) subsequently applied the name C. consobrina to English Pleistocene material in general.…”
Section: Introductionmentioning
confidence: 99%